The The Effect of Political Ideology on Public Administration Policy - Sarjito, Aris (Udayana Journal of Social Sciences and Humanities; Vol 7 No 2 (2023): Vol 7 No 2 (2023): UJoSSH, September 2023, 2024)
Abstract The relationship between political ideology and public administration policy has been studied extensively in the past few decades. Research has indicated that political actors play a crucial role in shaping public administration policy as they are the ones who are elected to represent the interests of the voters. Public opinion also plays an important role in shaping policy as it is the voice of the people who elect government officials. The aim of this study is to explore the correlation between political ideology and public administration policy, the impact of political actors on public administration policy, the role of public opinion in shaping public administration policy, and the effects of policy implementation on political ideology. The methodology employed in this study involves qualitative analysis of survey data obtained from a wide range of sources such as books, journals, and various documents. The findings of this study suggest that political ideology is strongly correlated with public administration policy. The impact of political actors on public administration policy is significant, with those in power often shaping policy to fit their own political agendas. Public opinion has a significant impact on policy formation, with policymakers often looking to cater their policies to the needs and desires of the electorate. Policy implementation has also been found to have a significant impact on political ideology, with policies that are successfully implemented often creating an ideological landscape that is difficult to change. Keywords: policy implementation, political actors, political ideology, public administration policy, public opinion.